PERILAKU PASIEN TERHADAP UPAYA PEMBERSIHAN KARANG GIGI DI BPG PUSKESMAS II DENPASAR TIMUR KOTA DENPASAR - Ni Wayan Arini (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Periodontal disease is the second largest illness stffired by the community in Indonesia (73.50%,,), one of its etiologies is tartar which is found in 46.2% of the population. The impact of periodontal disease on systemic health include cardiovascular disease, atherosclerosis, premature birth and low birth weight. The aim of this sludy is to analyze the factors related to patient's lurtur cleoning behavior on BPG Primary Health Center II, East Denpasur City.This study uses quantitative merhods with survey design and cross sectional approaches. Sample size is 185 people.Results showed the majority (70.3%0) of respondents did the less practice. Factors which connected to cleaning the tartar formation practice is (48,6%o) of respondent have middle educational level. Variables that are not associated with patient practice of tartar cleaning are age, sex, income, experience of toolhache, lrnowledge, attitudes.There is correlation behveen educational level and practice of factor tartar cleaning on BPG Primary Health Center II, East Denpasar City.